An adaptive LQG control for semi-active suspension systems. (12th May 2004) - Sohn, Hyun-Chul; Hong, Kyung-Tae; Hong, Keum-Shik; Yoo, Wan-Suk
In this paper, a road-adaptive LQG control for the semi-active Macpherson strut suspension system of hydraulic type is investigated. A new control-oriented model, which incorporates the rotational motion of the unsprung mass, is introduced. A semi-active suspension controller adapting to road variations is proposed. First, based on the extended least squares estimation algorithm, a LQG controller adapting to the estimated road characteristics is designed. Through the computer simulations, the performance of the proposed semi-active suspension is compared with that of a non-adaptive one. The results show better control performance of the proposed system over the compared one.